Factors that Influence Consumer’s Attitudes and Decision Making in Shopping for Halal Food - Nur Farhana, Mohamad Rasdi; Farah Dipah, Khalid; Jerome Kueh, Swee Hui; Joanne Shaza, Janang; Muhammad Asraf, Abdullah (Human Resource Management Academic Research Society (HRMARS), 2023)
This study aims to investigate the factors that influence consumers’ attitudes and decisionmaking in shopping for halalfood. These factorsinclude halal logo certification, social influence (word of mouth), and religious beliefs. The sample of consumers in this study is from Sibu, Sarawak targeting 300 random respondents via the questionnaire. Findings were assessed in terms of descriptive analysis, reliability test, Pearson correlation, and multiple regression. Results indicate that halal logo certificate, social influence (word of mouth), and religious belief have a significant positive relationship in the attitude and decision-making of consumers in shopping for halal food. The results provide some perspective to the industry players with information that will influence customers’ behavior and decision-making regarding Halal food.